2018
DOI: 10.1088/1361-6595/aac5b3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the gas flow rate on the spatiotemporal distribution of Ar(1s5) absolute densities in a ns pulsed plasma jet impinging on a glass surface

Abstract: This work presents spatial (axial-z and transversal-y) and temporal distributions of Ar(1s 5 ) metastable absolute densities in an atmospheric pressure argon micro-plasma jet impinging on an ungrounded glass surface. Guided streamers are generated with a DBD device driven by pulsed positive high voltages of 6 kV in amplitude, 224 3  ns in FWHM and 20 kHz in frequency. The argon flow rate is varied between 200 and 600 sccm. The glass plate is placed at 5 mm away from the reactor's nozzle and perpendicular to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(106 citation statements)
references
References 73 publications
8
98
0
Order By: Relevance
“…Figure illustrates the experimental setup used in this work. The APPJ was produced using a coaxial Dielectric Barrier Discharge (DBD) reactor, which has been described in more detail elsewhere . Briefly, it contained a quartz dielectric tube and a stainless‐steel hollow cylinder (biased electrode), which was placed tightly inside the quartz tube.…”
Section: Experimental Setup and Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure illustrates the experimental setup used in this work. The APPJ was produced using a coaxial Dielectric Barrier Discharge (DBD) reactor, which has been described in more detail elsewhere . Briefly, it contained a quartz dielectric tube and a stainless‐steel hollow cylinder (biased electrode), which was placed tightly inside the quartz tube.…”
Section: Experimental Setup and Techniquesmentioning
confidence: 99%
“…But, again, this was done in the absence of a target and without giving any information about the radial distribution of the Ar(1s 5 ) absolute density. It should be noted that our group has studied recently a ns‐pulsed Ar APPJ impinging on a floating‐potential glass plate . It was demonstrated that the residual plasma column left by the streamers is well diffuse and reproducible.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations